Women and entrepreneurship in Mali: towards an understanding of motivations and obstacles in the informal sector - Silamakan KANTE (المجلة الدولية للأداء الاقتصادي)
This research paper explores the motivations and obstacles faced by women entrepreneurs in Mali’s informal sector. Adopting a qualitative approach, the study conducted semi-structured interviews with fifteen women entrepreneurs operating in commercial and service activities within two neighborhoods of the Kati region. Thematic analysis, facilitated by NVIVO 21, revealed that women predominantly engage in subsistence entrepreneurship driven by necessity, aiming to support themselves and their families amidst limited employment alternatives and low educational attainment. Key obstacles identified include significant challenges in accessing finance, difficulties in securing clientele, high tax burdens, and the struggle to balance business with domestic responsibilities. Most participants relied on personal savings, informal savings groups (tontines), and family support rather than formal banking services, reflecting both a fear of indebtedness and limited trust in financial institutions. The lack of entrepreneurial support and business training further constrains business growth and sustainability. The findings underscore the importance of targeted policy interventions, improved access to formal financing, and enhanced support services to empower female entrepreneurs and promote the formalization and resilience of their enterprises.